KORELASI ANTARA PENGETAHUAN PERBAIKAN MOTOR OTOMOTIF DAN PRESTASI KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA SISWA KELAS XI TEKNIK OTOMOTIF SMK MA’ARIF 1 KROYA CILACAP JAWA TENGAH TAHUN PELAJARAN 2013/2014 - Joni Setiawan; Slamet Priyanto (Universitas Sarjanawiyata Tamansiswa, 2015)
The objectives of this study were to describe (1) correlation between knowledge of automotive motor repair with entrepreneur interest; (2) correlation between entrepreneurship learning achievement with entrepreneur interest; and (3) correlation between knowledge of automotive motor repair and entrepreneurship learning achievement with entrepreneur interest among the eleventh grade students of SMK Ma-Arif 1 Kroya Cilacap Central Java in academic year 2013/2014. This study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used regression. This study shows that (1) there was a positive and significant between knowledge of automotive motor repair with entrepreneur interest; (2) there was a positive and significant between entrepreneurship learning achievement with entrepreneur interest; and (3) there was a positive and significant between knowledge of automotive motor repair and entrepreneurship learning achievement with entrepreneur interest among the eleventh grade students of SMK Ma-Arif 1 Kroya Cilacap Central Java in academic year 2013/2014.Â